Left Ventricular Noncompaction - Beny Togatorop; Amiliana M Soesanto (Jurnal Kardiologi Indonesia, 2012)
In normal human hearts of children and adults the leftventricle (LV) has up to 3 prominent trabeculations andis, thus, less trabeculated than the right ventricle. Rarely, more than 3 prominent trabeculations that is theso-called LV noncompaction of ventricular myocardium(NVM) can be found at autopsy and by various imaging techniques including echocardio graphy and MRI etc.NVM is recently included in the 2006 classsification of cardiomyopathies as a Genetic Cardio myopathy. NVMoccurs because of a disorder of endomyocardial morphogenesisthat results in a failure of trabecular compaction ofthe developing myocardium. In adult patients one ormore segments, especially the apical, mid-lateral and midinferiorregions, of the left ventricle, and sometimes bothventricles, are characterized by numerous sinusoids ortrabeculae that are excessive in number and abnormal inprominence and by deep intratrabecular recesses covered by endothelium that exhibits continuity with ventricular endocardium. Numerous modalities have been used in the description, characterization, and diagnosis of NVM including, but not limited to, magnetic resonance imaging, two-dimensional echocardiography (2DE), contrast- enhanced 2DE, and angiography. 2DE is by far the most commonly used diagnostic modality. On thebasis of echocardiographic studies, the prevalence of NVMhas been estimated at 0.05% in the general population.